Thymic Carcinoid in a Patient with Concurrent Manifestations of Multiple Endocrine Neoplasia Type 1 - Jasmine Zhu; Samantha Dean; Umbreen Hafeez; Sandra Neoh (Case Reports in Endocrinology, 2023)
Thymic carcinoid tumours, especially in the context of multiple endocrine neoplasia type 1 (MEN 1), present significant clinical challenges due to their rarity and aggressive nature. This case report describes a complex patient with MEN 1, who suffered from multiple manifestations of the disease, including thymic carcinoid. The tumour was initially resected and treated with adjuvant radiotherapy. Due to slow progression over the years, the tumour was treated with two lines of chemotherapy before the patient succumbed to progressive disease. There is currently limited evidence favoring any specific medical treatment for thymic carcinoid.